“Calcium bombs” as harbingers of synaptic pathology and their mitigation by magnesium at murine neuromuscular junctions - Dissanayake, Kosala N.; Redman, Robert R.; Mackenzie, Harry; Eddleston, Michael; Ribchester, Richard R. (Frontiers in Molecular Neuroscience, 2022)
Excitotoxicity is thought to be an important factor in the onset and progression of amyotrophic lateral sclerosis (ALS). Evidence from human and animal studies also indicates that early signs of ALS include degeneration of motor nerve terminals at neuromuscular junctions (NMJs), before degeneration of motor neuron cell bodies. Here we used a model of excitotoxity at NMJs in isolated mouse muscle, utilising the organophosphorus compound omethoate, which inhibits acetylcholinesterase activity. Acute exposure to omethoate (100 µM) induced prolonged motor endplate contractures in response to brief tetanic nerve stimulation at 20-50Hz. In some muscle fibres, Fluo-4 fluorescence showed association of these contractures with explosive increases in Ca2+ (“calcium bombs”) localised to motor endplates. Calcium bombs were strongly and selectively mitigated by increasing Mg2+ concentration in the bathing medium from 1 mM to 5 mM. Overnight culture of nerve-muscle preparations from WldS mice in omethoate or other organophosphorus insecticide components and their metabolites (dimethoate, cyclohexanone and cyclohexanol) induced degeneration of NMJs. This degeneration was also strongly mitigated by increasing [Mg2+] from 1 mM to 5 mM. Thus, equivalent increases in extracellular [Mg2+] mitigated both postsynaptic calcium bombs and degeneration of NMJs. The data support a link between Ca2+ and excitotoxicity at NMJs and suggest that elevating extracellular [Mg2+] could be an effective intervention in treatment of synaptic pathology induced by excitotoxic triggers.